Rheumatic Exercise as a Nonpharmacological Therapy in Reducing Pain Rheumatoid Arthritis in the Elderly - Kurnia, Ilham; Etlidawati (Proceedings Series on Health & Medical Sciences, 2025)
Changes that occur in the elderly include physical changes, including physical disorders such as Rheumatoid Arthritis (RA). RA can be triggered by several stress factors, such as surgery and trauma, and often appears suddenly. The highest incidence of rheumatism is in the elderly, this shows that rheumatism increases with age. One of the non-pharmacological therapies to reduce rheumatic pain is rheumatic exercise. Qualitative research type, descriptive design with case study. Number of samples in the study of 5 respondents with total sampling technique. The data was analyzed and presented in the form of a frequency distribution table. Results: Respondent characteristics based on age showed that the majority were over 60 years old (80%). All respondents were female (100%), and the majority worked as farmers (60%). The average highest pain scale before rheumatic exercise was 4.6 and the highest after 3 days of rheumatic exercise was 3.3. Rheumatic exercise therapy can reduce the pain scale in elderly patients suffering from Rheumatoid Arthritis.